OPINI AUDITOR SEBAGAI PEMODERASI PENGARUH GOOD CORPORATE GOVERNANCE PADA NILAI PERUSAHAAN PERBANKAN TAHUN 2012-2014 - Udiyani Putri, Putu Shinta; Dwija P, I Gst. Ayu Made Asri (E-Jurnal Akuntansi; Vol 17 No 1 (2016), 2016)
This study aims to determine the ability of the auditor's opinion moderating influence on the value of good corporate governance of the company. This study uses data analysis techniques Moderated Regression Analysis with a total sample of 27 banking companies listed in Indonesia Stock Exchange with the observation period from 2012 to 2014, bringing the total to 81 sampel. The observational studies indicate that institutional ownership, managerial ownership and the audit committee a positive effect on the value of the company. While the research results of good corporate governance which is proxied by independent board suggests that the independent board has no effect on the value of the company. The auditor's opinion as a moderating influence on the value of good corporate governance the company shows a positive result, which means the audit opinion is able to moderate the influence of good corporate governance in the company's value.
Keywords: good corporate governance, the auditor' s opinion, the value of the company